Effect of Bottom Ash and Cow Manure Compost on Chemical Properties of Soil at New-Established Rice Field - Nurmegawati Nurmegawati; Iskandar Iskandar; Sudarsono Sudarsono (Universitas Sebelas Maret, 2019)
The conversion of dryland to rice field at Sumatra Island, Indonesia was generally developed on marginal lands with Ultisols and Oxisols soil types. Those soil types contained high iron (Fe) and aluminum (Al), but low phosphorus (P) and potassium (K). That is because the changes in the process resulted from submerging the soil. For example, the decrease of redox potential, ion reduction from Fe3+ to Fe2+, and Mn4+ into Mn2+. Those compounds will be dissolved and can be absorbed by plants thus causing toxicity. The objective of the study was to assess the effects of bottom ash and cow manure compost at the various doses on soil chemical properties and rice yield on the new-established rice field. This research used factorial design with two factors in Completely Randomized Design. The factors were a dose of bottom ash and cow manure compost, with three replications. The results showed. The addition of bottom ash and cow manure compost at the dosage in this study was not able to reduce the levels of FeDTPA and MnDTPA at newly established rice fields. However, the application of cow manure compost significantly increased soil pH, exchangeable cation (K, Na, Ca), base saturation and decreased exchangeable-H. The addition of bottom ash does not affect paddy yield, while cow manure compost up to 10 tons ha-1 increased panicle and straw dry weight.